Intimate molecular interactions of P. falciparum merozoite proteins involved in invasion of red blood cells and their implications for vaccine design (2008)
A first step in the development of a logical and rational methodology for obtaining vaccines against the threatening effects of malaria has been a thorough analysis of the intimate molecular interactions of the molecules involved in P. falciparum's invasion of red blood cells (RBC) including secondary and 3D structure determination of some of them. Blocking the interactions could specifically be induced by activating the immune system with these molecules. Developing a completely effective vaccine against the parasite's blood stage must therefore involve a similar number of conserved high-activity bending peptides (HABPs) derived from some of the proteins that are directly involved in RBC invasion being blocked by the immune system. Data on the number of HABPs, their presence, processed and released fragments, network interactions, and merozoite-membrane-rafts shows the complexity of the processes involved in merozoite invasion of RBCs.